Co-assembled hybrid of carbon nanodots and molecular fluorophores for efficient solar-driven water evaporation. (31st October 2022) - Nhat Hang, Nguyen Thi; Van Canh, Nguyen; Hoa, Nguyen Hiep; Du, Pham Dinh; Le, Phuoc Huu; Nguyen, Vanthan
Abstract: Solar-driven water evaporation has attracted tremendous attention for its potential applications in desalination, electricity generation, and sterilization. However, low efficiency, high cost, and low stability of solar-to-heat converting materials make it difficult for large-scale manufacturability. Herein, we propose carbon nanodots (CDs)/molecular fluorophores hybrid material with high solar-to-heat conversion efficiency, low cost, and large-scale production for efficient solar-driven water evaporation. The CDs/Fluorophores hybrid was synthesized at gram-scale by drying product solution obtained from hydrothermal synthesis of CDs. The CDs/Fluorophores hybrid exhibited a broad absorption spectrum range from the UV–Vis to NIR region in solid state with the internal solar-to-heat conversion efficiency of up to 98.8%. Furthermore, we fabricated an interfacial water evaporation structure using CDs/Fluorophores-coated paper. The evaporation system exhibited a high evaporation rate of 2.1 kg m −2 h −1 and solar-to-vapor energy efficiency of 133.9% under one sun irradiation. Our results suggest that CDs/Fluorophores hybrid is a very promising photothermal material for a series of practical applications in solar-driven water evaporation, photothermal catalysis, and photothermal therapy. Graphical abstract: Image 1